Race- and Sex-Specific Population Attributable Fractions of Incident Heart Failure: A Population-Based Cohort Study From the Lifetime Risk Pooling Project. (25th March 2021) - Sinha, Arjun; Ning, Hongyan; Carnethon, Mercedes R.; Allen, Norrina B.; Wilkins, John T.; Lloyd-Jones, Donald M.; Khan, Sadiya S.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Race- and sex-specific differences in heart failure (HF) risk may be related to differential burden and effect of risk factors. We estimated the population attributable fraction (PAF), which incorporates both prevalence and excess risk of HF associated with each risk factor (obesity, hypertension, diabetes, current smoking, and hyperlipidemia), in specific race-sex groups. Methods: A pooled cohort was created using harmonized data from 6 US longitudinal population-based cohorts. Baseline measurements of risk factors were used to determine prevalence. Relative risk of incident HF was assessed using a piecewise constant hazards model adjusted for age, education, other modifiable risk factors, and the competing risk of death from non-HF causes. Within each race-sex group, PAF of HF was estimated for each risk factor individually and for all risk factors simultaneously. Results: Of 38 028 participants, 55% were female and 22% Black. Hypertension had the highest PAF among Black men (28.3% [95% CI, 18.7%–36.7%]) and women (25.8% [95% CI, 16.3%–34.2%]). In contrast, PAF associated with obesity was the highest in White men (21.0% [95% CI, 14.6%–27.0%]) and women (17.9% [95% CI, 12.8%–22.6%]). Diabetes disproportionately contributed to HF in Black women (PAF, 16.4% [95% CI, 12.7%–19.9%]). The cumulative PAF of all 5 risk factors was the highest in Black women (51.9% [95% CI, 39.3%–61.8%]). Conclusions: The observed differences in contribution of risk factors across race-sex groups can inform tailored prevention strategies to mitigate disparities in HF burden. This novel competing risk analysis suggests that a sizeable proportion of HF risk may not be associated with modifiable risk factors.